Buckling-restrained brace using steel mortar planks; performance evaluation as a hysteretic damper. - Iwata, Mamoru (Earthquake engineering & structural dynamics.)
The authors developed a buckling-restrained brace that enables increased design freedom at both ends of the core plate and strict quality control while providing stable hysteresis characteristics even under high strains. The buckling-restrained brace can be formed by welding a core plate covered with unbonded material to a pair of mortar-filled channel steels (steel mortar planks) as a restraining part. The use of this approach enables visual confirmation of the status of the mortar filling and also facilitates standardizing structural members and member-by-member quality control. Specimens of a buckling-restrained brace with different steel mortar plank heights are fabricated to adjust the restraining force, along with specimens with different core plate width-to-thickness ratios. The tests were conducted to reveal the hysteretic characteristics of the braces, as well as their cumulative plastic strain energy, elastoplastic properties, and stiffening properties. A performance evaluation formula as well as a buckling-restrained brace design method using the test results is proposed.